The Bioinformatics Virtual Coordination Network: An Open-Source and Interactive Learning Environment - Tully, Benjamin J.; Buongiorno, Joy; Cohen, Ashley B.; Cram, Jacob A.; Garber, Arkadiy I.; Hu, Sarah K.; Krinos, Arianna I.; Leftwich, Philip T.; Marshall, Alexis J.; Sieradzki, Ella T.; Speth, Daan R.; Suter, Elizabeth A; et al. (Frontiers in Education, 2021)
Lockdowns and ‘stay-at-home’ orders shuttered bench and field dependent research across the world as a consequence of the global COVID-19 pandemic. The pandemic continues to have an impact on research progress and career development, especially for graduate students and early career researchers, as strict social distance limitations stifle ongoing research and impede in-person educational programs. The goal of the Bioinformatics Virtual Coordination Network (BVCN) was to reduce some of these impacts by helping research biologists learn new skills and initiate computational projects as alternative ways to carry out their research. The BVCN was founded in April 2020 by an international group of early-career microbiology researchers with expertise in bioinformatics and computational biology. The BVCN instructors identified foundational bioinformatic topics and organized hands-on tutorials through cloud-based platforms, such as RStudio Cloud and MyBinder. The major topics included the Unix terminal, R and Python programming languages, amplicon analysis, metagenomics, functional protein annotation, transcriptome analysis, network science, and population genetics and comparative genomics. The BVCN was structured as an open-access resource with a central hub providing access to all lesson content and hands-on tutorials (https://biovcnet.github.io/). As laboratories reopened, the BVCN evolved: while the platform continues to enable ‘a la carte’ lessons for learning computational skills, new and ongoing collaborative projects were initiated among instructors and participants. In this manuscript we discuss the history, successes, and challenges of the BVCN initiative, highlighting how the lessons learned and strategies implemented may be applicable to the development and planning of future courses, workshops, and training programs.